EU consumer law and policy - Weatherill, Stephen 1961- (Elgar, 2005)
In many respects the consumer is supposed to be the ultimate beneficiary of the process of market integration in Europe, but the EC Treaty has never included an elaborate recognition of how the EU serves the consumer interest. This highly esteemed book, now in its second edition, provides a comprehensive and up-to-date introduction to the subject, explaining the evolution of consumer law and policy in the EC in terms of both legislative and judicial activity. The book also situates EC consumer law and policy within its broader social, political and economic context, providing a window to a range of wider issues (and tensions) relating to Community regulatory strategies and their effect on the member states. This readable yet critically sound textbook will be gratefully received by readers familiar with the first edition and will be indispensable for both postgraduate and undergraduate students of EC law. It will appeal to all academics, regulators and practising lawyers with an interest in EU trade law or indeed European law more generally.
Früher u.d.T.: Weatherill, Stephen: EC consumer law and policy
Includes bibliographical references and index
Keywords: Europäische Union; aConsumer protection xLaw and legislation zEuropean Union countries; Recht; Consumer protection -- Law and legislation -- European Union countries; Verbraucherschutz; Verbraucherpolitik; Europäische Union. Mitgliedsstaaten